USING INNOVATIVE TRAINING METHODS IN THE CONDITIONS OF DISTANCE EDUCATION - Barlai, Anna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article presents the author’s generalization regarding the specifics of the use of innovative teaching methods, taking into account development trends and the importance of socially (community) oriented education in the conditions of distance education in Ukraine. Certain aspects of the use of innovative methods of interactive exercises using learningapps.org, Edmodo, the Case-Study method, and the method of mental maps are highlighted.